Development of the method for the pharmaceutical availability testing of clotrimazole from multiphase semi-solid vaginal dosage forms - Michał Smoleński; Dorota Haznar-Garbacz; Susanne Florin-Muschert; Katarzyna Małolepsza-Jarmołowska (Polish Pharmaceutical Society, 2023)
Introduction: The intravaginal drug administration enables treatment of the local and systemic diseases. The anatomy and physiology of a vagina provide several difficulties for drug technologists due to the small amount and continuous production of vaginal discharge, especially in the case of lipophilic drugs often characterized by insufficient solubility. The application of poorly soluble drug substances in the form of nanoemulsions improves their availability. However, in the case of nanoemulsion-based vaginal dosage forms, no standardized methods have been defined for testing the amount of a drug released from encapsulated form. Aim of the study: Comparison and development of a method for testing the availability of active pharmaceutical substances from vaginal nanoemulsion-based drug forms. Materials and methods: The nanoemulsion and reference products (cream and suspension) were placed in a dialysis bag separating them from the acceptor medium. The changes in the concentration of the free fraction of the model active substance - clotrimazole were assessed. The experiments were performed using 2 static methods of different mixing method (magnetic stirring and USP apparatus III) and 2 dynamic methods including the flow of the medium through the flow-through cell at 2 mL/min and 2 mL/h. The experiments were conducted for 5 h. Results: Incomplete release of the active pharmaceutical ingredient was observed for all tested formulations over the experiment. Despite the delivery of a fresh portion of the medium, low concentrations of the free clotrimazole fraction were observed for both flow-through methods i.e., a maximum of about 7.5% of the dose for the 2 mL/min flow rate and 5% for the 2 mL/h flow rate. In stationary methods, the maximum recorded concentrations of the free fraction of the drug corresponded to approx. 25% of the initial amount. For the pilot stationary method, high standard deviations (SD) were observed, which affected the low discriminatory properties of the method. The method based on the reciprocating cylinder dissolution apparatus provided results exhibiting smaller SD and more significant differences between the tested formulations. The highest concentrations among the evaluated formulations were observed for nanoemulsion or nanoemulsion and suspension, depending on the used test technique. Significantly lower doses of the drug were released from the cream in almost every test. Conclusions: The selection of the method used to assess the pharmaceutical availability of an active pharmaceutical ingredient has a crucial impact on the release profiles obtained. The stationary method using a reciprocating cylinder apparatus (USP apparatus III) had the highest measurement precision and provided the most discriminatory results.